INTEGRATED MEDICAL CURRICULUM: A REVIEW OF UNIVERSITY OF HEALTH SCIENCES CURRICULUM - Iqbal, Tehseen (Pakistan Journal of Physiology, 2018)
To study the phenomenon of disease without books is to sail an uncharted sea, while to study books without patients is not to go to sea at all. Sir William Osler (1849-1919) Integration can be defined as integration of content within a single lecture or integration of a medical school's curriculum. MBBS curriculum of University of Health Sciences seems to be on the basis of Z-shaped curriculum model. Pakistani medical schools are unique in the sense that all teachers of basic medical sciences are physicians having MBBS degree and Faculty have additional post-graduate qualification in the relevant basic subject. Horizontal integration takes place when students prepare for annual examination, when all subjects are learned at the same time. During their lectures, these physician-teachers cross reference for horizontal integration and relate basic concepts with clinical situations for vertical integration. In the UHS curriculum, clinical modules and clinical skills are taught to further facilitate vertical integration. We propose a simple scheme to rationalize integration in the annual assessment. In the first year class only 10% questions may be integrated, clinical scenario based; subsequently 20% increase each year will give the ratios of 30%, 50%, 70% and 90%. To improve medical education in the country, the only way forward is to efficiently train teachers, recruit good teachers, authorize, trust and respect teachers.